A Randomized Controlled Trial Comparing the Effects of Yoga With an Active Control on Ambulatory Blood Pressure in Individuals With Prehypertension and Stage 1 Hypertension. Issue 1 (4th January 2014) - Hagins, Marshall; Rundle, Andrew; Consedine, Nathan S.; Khalsa, Sat Bir S.
<x xml:space="preserve">Abstract</x> The purpose of this study was to compare the effects of yoga with an active control (nonaerobic exercise) in individuals with prehypertension and stage 1 hypertension. A randomized clinical trial was performed using two arms: (1) yoga and (2) active control. Primary outcomes were 24‐hour day and night ambulatory systolic and diastolic blood pressures. Within‐group and between‐group analyses were performed using paired t tests and repeated‐measures analysis of variance (time × group), respectively. Eighty‐four participants enrolled, with 68 participants completing the trial. Within‐group analyses found 24‐hour diastolic, night diastolic, and mean arterial pressure all significantly reduced in the yoga group (−3.93, −4.7, −4.23 mm Hg, respectively) but no significant within‐group changes in the active control group. Direct comparisons of the yoga intervention with the control group found a single blood pressure variable (diastolic night) to be significantly different (P=.038). This study has demonstrated that a yoga intervention can lower blood pressure in patients with mild hypertension. Although this study was not adequately powered to show between‐group differences, the size of the yoga‐induced blood pressure reduction appears to justify performing a definitive trial of this intervention to test whether it can provide meaningful therapeutic value for the management of hypertension.